2021
DOI: 10.3390/cells10092268
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of the Ubiquitin Specific Proteases USP43, USP41, USP27x and USP6 in Osteosarcoma Cell Lines: Inhibition of Osteosarcoma Tumor Growth and Lung Metastasis Development by the USP Antagonist PR619

Abstract: Osteosarcoma (OS) is the most common malignant bone tumor in children and teenagers. In many cases, such as poor response to treatment or the presence of metastases at diagnosis, the survival rate of patients remains very low. Although in the literature, more and more studies are emerging on the role of Ubiquitin-Specific Proteases (USPs) in the development of many cancers, few data exist regarding OS. In this context, RNA-sequencing analysis of OS cells and mesenchymal stem cells differentiated or not differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 50 publications
2
12
0
Order By: Relevance
“…Recent studies have analyzed overall survival of cancer patients according to expression of USP41 based on The Cancer Genome Atlas (TCGA) database and suggested USP41 as marker predicting prognosis especially in invasive breast cancer and lung cancer [ 23 , 24 ]. Even though some researchers have reported that USP41 promotes cancer cell migration and proliferation [ 25 , 26 ], the underlying specific mechanism to cancer migration and EMT is still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have analyzed overall survival of cancer patients according to expression of USP41 based on The Cancer Genome Atlas (TCGA) database and suggested USP41 as marker predicting prognosis especially in invasive breast cancer and lung cancer [ 23 , 24 ]. Even though some researchers have reported that USP41 promotes cancer cell migration and proliferation [ 25 , 26 ], the underlying specific mechanism to cancer migration and EMT is still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Patients with PDAC have a poor prognosis, highlighting the need to develop innovative therapeutic strategies for this aggressive illness [25]. USPs are the largest DUBs family and a growing number of studies show that various USPs may be important targets for cancer therapy due to their ability to regulate tumor formation, including tumor growth and the process of metastasis [16,17,19,20,[26][27][28]. Previous research indicates that USP43, a member of the USPs family, plays a significant role in breast cancer, CRC, lung squamous cell carcinoma, and nonsmall cell lung cancer can promotes tumor migration, invasion, and associated with a poor prognosis [22,[29][30][31].…”
Section: Discussionmentioning
confidence: 99%
“…Through statistical studies, Lavaud et al. found that patients with highly expressed USP6 and USP41 had significantly decreased survival ( 100 ). BRCA1-associated protein-1 (BAP1), an important nucleus-associated deubiquitinating enzyme, was significantly decreased in osteosarcoma, and was able to affect metastasis and invasion of osteosarcoma cells by regulating the PI3K/AKT pathway ( 101 ).…”
Section: Ubiquitination/deubiquitination In Osteosarcomamentioning
confidence: 99%